1973
DOI: 10.2135/cropsci1973.0011183x001300060028x
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Germinating Maize Pollen to Helminthosporium maydis Pathotoxins1

Abstract: Pollen from fertile plants of corn (Zea mays L.), with normal and restored male‐sterile cytoplasm (cms), from various sources was assayed for in vitro germination on media containing Helminthosporium maydis pathotoxins extracted from infected leaves. The “pathotoxin” from H. maydis race O inhibited neither germination nor growth of pollen from any of the cms or normal cytoplasm sources tested, as compared with controls. The pathotoxin from H. maydis race T, however, inhibited in vitro germination and growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…It had been suggested (13), but later modified (2), that the primary effect may lie in a disturbance of mitochondrial oxidation. A mitochondrial target site would be consistent with increased leakage of ions (6,7) and inhibition of root growth and pollen tube elongation (11) of corn susceptible to the toxin. In addition to these effects, a drop in transpiration and photosynthetic rates caused by toxin was ascribed to stomatal closure induced by alteration of K+ flux in guard and subsidiary cells (1).…”
mentioning
confidence: 85%
“…It had been suggested (13), but later modified (2), that the primary effect may lie in a disturbance of mitochondrial oxidation. A mitochondrial target site would be consistent with increased leakage of ions (6,7) and inhibition of root growth and pollen tube elongation (11) of corn susceptible to the toxin. In addition to these effects, a drop in transpiration and photosynthetic rates caused by toxin was ascribed to stomatal closure induced by alteration of K+ flux in guard and subsidiary cells (1).…”
mentioning
confidence: 85%
“…During the development of the augmented K+ uptake capacity in either N or T roots, the sensitivity to the toxin did not change; uptake in N roots was inhibited by 10 to 25% and uptake in T roots was inhibited by 70 to 80%. The difference in toxin sensitivity of K+ uptake between N and T roots may be due to N possessing a protective mechanism which is deficient in T.The extreme susceptibility of Texas cytoplasmic male-sterile (T) maize to Southern Corn Leaf Blight is cytoplasmically conditioned and inherited in association with the non-Mendelian determinant of male sterility (12,18). T versions of a given maize inbred are more susceptible to Helminthosporium maydis, race T than normal cytoplasmic (N) versions (7, 10).…”
mentioning
confidence: 99%
“…It has been shown that a toxin from Drechslera maydis prevented germination of pollen from maize plants susceptible to the disease but not of pollen from resistant plants (30), and compounds present in Alternaria brassicicola culture filtrates inhibited Brassica pollen germination (6). In very few cases (5,30) has it been possible to make pollinations with selected pollen. Success has previously been limited because the selection procedure killed the pollen-producing plants (but not in ref.…”
Section: Discussionmentioning
confidence: 99%